Inovasi E-LKPD Berbantuan Liveworksheets Materi Daerahku Kebanggaanku sebagai Penguatan Pembelajaran IPAS di Sekolah Dasar - Filza Mulya Rahma; Yusra Nasution; Wildansyah Lubis; Husna Parluhutan Tambunan; Waliyul Maulana Siregar (Universitas Negeri Medan, 2025)
This study aims to develop and examine the validity, practicality, and effectiveness of a Liveworksheets-based Electronic Student Worksheet (E-LKPD) on the topic